2016
DOI: 10.1111/apm.12536
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and bilateral kidney tumors with clear cells of three different histotypes: A case report with clinicopathologic and molecular study

Abstract: We describe a rare multicentric neoplastic disease arising bilteraly in the kidney. The patient was a 70-year-old man, who, during a period of 3 years, was treated for five independent tumors of three histotypes (three multilocular cystic clear cell renal cell neoplasms of low malignant potential, one clear cell renal cell carcinoma, and one clear cell papillary renal cell carcinoma, respectively). Pathologic diagnosis of the reported tumors was confirmed by immunohistochemical analyses, including CD10, CA IX,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
0
6
1
Order By: Relevance
“…found that no KRAS mutation occurs in clear cell renal cell carcinoma ( n = 48), PRCC type 1 ( n = 1) and chromophobe renal cell carcinoma ( n = 1). KRAS mutations in renal cell carcinoma are only seen in sporadic reports 33 . In the current study, KRAS mutations accounted for only 0.7% (two of 279) of PRCCs and for 0.2% (one of 451) of clear cell renal cell carcinomas in the TCGA database.…”
Section: Discussioncontrasting
confidence: 46%
“…found that no KRAS mutation occurs in clear cell renal cell carcinoma ( n = 48), PRCC type 1 ( n = 1) and chromophobe renal cell carcinoma ( n = 1). KRAS mutations in renal cell carcinoma are only seen in sporadic reports 33 . In the current study, KRAS mutations accounted for only 0.7% (two of 279) of PRCCs and for 0.2% (one of 451) of clear cell renal cell carcinomas in the TCGA database.…”
Section: Discussioncontrasting
confidence: 46%
“…Varied papillary lesions, including intraductal papillary mucinous neoplasms of the pancreas and urothelial papillomas of the bladder, also have frequent KRAS mutations [10,11]. KRAS mutations in RCCs are very rare and have only been seen in sporadic reports [12].…”
Section: Discussionmentioning
confidence: 99%
“…recommend extensive molecular profiling in cases with multiple lung cancers, as it might clarify the association between the lung lesions found . Several investigators have reported the utility of molecular biological analysis for diagnosis and treatment in multiple primary cancers, not only in lung cancer but also breast, gastric, hepatocellular, renal, and colorectal cancers . Thus, molecular biological analysis is necessary when multiple cancers of the same histotype are identified in the same tissue where there are multiple primary tumors.…”
Section: Discussionmentioning
confidence: 99%